Sektor szkła płaskiego jako sektor globalny - próba analizy - Tańcula, Anna (The Flat Glass Sector as a Global Sector - an Attempt of Analysis, 2008)
The paper focuses on the global sectors which create possibilities of implementing the global strategies. The study comprises of three parts: a theoretical explanation of global sector’s nature, the characteristic of flat glass sector and the evaluation of its globalizing potential. The author’s aim is to present a practical application of the idea of factors determining the sector’s globalizing potential. The evaluation of the globalizing potential of the flat glass sector answers the question whether it is possible to implement a global strategy in this particular sector.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 386-395